2022
DOI: 10.1097/dcr.0000000000002450
|View full text |Cite
|
Sign up to set email alerts
|

Limits of Clinical Restaging in Detecting Responders After Neoadjuvant Therapies for Rectal Cancer

Abstract: BACKGROUND:Accurate clinical restaging is required to select patients who respond to neoadjuvant chemoradiotherapy for locally advanced rectal cancer and who may benefit from an organ preservation strategy. OBJECTIVE:The purpose of this study was to review our experience with the clinical restaging of rectal cancer after neoadjuvant therapy to assess its accuracy in detecting major and pathological complete response to treatment. DESIGN:This was a retrospective cohort study. SETTING:This study was conducted at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…Deidda et al 12 reported the results from 2 high-volume Italian centers with respect to the accuracy of clinical criteria to assess major and complete response to neoadjuvant therapy. Bedrikovetskiv et al 13 reported on data from 2 Australian tertiary care centers and showed that sarcopenia was not a predictor of poor response to neoadjuvant chemoradiation in patients with LARC.…”
Section: Predictors Of Response After Neoadjuvant Therapy/restagingmentioning
confidence: 99%
“…Deidda et al 12 reported the results from 2 high-volume Italian centers with respect to the accuracy of clinical criteria to assess major and complete response to neoadjuvant therapy. Bedrikovetskiv et al 13 reported on data from 2 Australian tertiary care centers and showed that sarcopenia was not a predictor of poor response to neoadjuvant chemoradiation in patients with LARC.…”
Section: Predictors Of Response After Neoadjuvant Therapy/restagingmentioning
confidence: 99%